Associations between body mass index, waist circumference and body shape index with resting blood pressure in Portuguese adolescents. (March 2013) - Duncan, Michael J.; Mota, Jorge; Vale, Susana; Santos, Maria Paula; Ribeiro, Jose Carlos
<x xml:space="preserve">Abstract</x> Background: Elevated blood pressure (BP) in childhood and adolescence is associated with overweight and obesity. Recently a body shape index (ABSI) has been suggested as superior to body mass index (BMI, kg/m2) and waist circumference (WC) as a measure of disease risk. Objective: To examine the association between ABSI, BMI, WC and BP in Portuguese adolescents and to consider the role of ABSI, BMI and WC when examining this issue in adolescents. Methods and procedures: Height, body mass, WC and resting blood pressure were assessed in 445 Portuguese adolescents (252 girls and 193 boys) aged 10–17 years. Results: ABSI, BMI and WC were all significantly related to both SBP and DBP (all p = 0.001 or better). ABSI, BMI and WC were all significant predictors of SBP and DBP for the whole sample and when analysed in separate gender groups (p = 0.001 or better in all cases). However, in all cases ABSI was a better predictor of BP than BMI or WC. Conclusions: Although BMI and WC significantly predict resting BP in adolescents, the use of ABSI explained a greater amount of the variance in BP in this population. When examining the effect of weight status on BP, researchers should consider use of ABSI alongside BMI.